Psycho-social correlates of physical activity in young adolescents - S. P., Dan; M. T., Mohd Nasir (Nutrition Society of Malaysia, 2008)
A cross-sectional study was conducted to determine the association between demographic and psychosocial factors with physical activity levels of four hundred, 13 year-old adolescents in Kuantan, Pahang, Malaysia. Physical Activity Questionnaire for Older Children (PAQ-C) was used to assess physical activity levels among the participants. The respondents comprised 41.8% males and 58.2% females encompassing 56.2% Malays, 42.0% Chinese, and 1.8% Indians. More than one third of the respondents were in the low physical activity level, most (61.5%) were in the moderate category and only 3.0% were in the high physical activity level. Males were more physically active than females (c2=23.667, p=0.0001). Female adolescents (45.1%) were twice as many as male respondents (22.1%) to fall in the low physical activity level category. Physical activity level was not correlated with ethnicity, but there was a significant interaction effect of sex and ethnicity in mean physical activity score (F=8.343, p=0.004) which indicated that Malay males had a higher mean physical activity score compared to Chinese males while Chinese females had a higher mean physical activity score than Malay females. For psycho-social factors, physical activity was positively correlated with physical activity self-efficacy (r=0.496, p=0.0001), peer influence (r=0.468, p=0.0001), family influence (r=0.298, p=0.0001) and beliefs for physical activity outcome (r=0.207, p=0.0001) while negatively associated with depression (r=-0.116, p=0.021) and body size discrepancy (r=-0.143, p<0.01). Further, respondents who had a better perception of their current health status were more physically active (c2=21.062, p=0.0001). However, physical activity was not correlated with perception of weight status and body parts satisfaction. Multivariate analysis showed that physical activity self-efficacy, sex and peer influence were found to be significant in explaining physical activity among adolescents. Findings from this study suggest that physical activity intervention should include physical activity self-efficacy and social influence components in interventions designed to promote regular physical activity in adolescence.